(untitled) (Damascus University Journal for engineering sciences, 2025)
In this research, the effect of (TiO2) on polyvinyl chloride (PVC) pipes exposed to sunlight was studied. Samples loaded with different percentages of this material were manufactured and exposed to (UV) rays presented in sunlight, which cause the decomposition of PVC by means of a Aging device. containing fluorescent tubes, and then conducting some mechanical and thermal tests (tensile and elongation, hardness, internal pressure, fall weights, longitudinal rebound (thermal effect), plasticizing point (VICAT Softening), where the results showed that samples containing (TiO2) 1.5-2.5% It showed the best mechanical and thermal properties.